'They can't empower us': The role of allies in the consumer movement. (4th March 2019) - Juntanamalaga, Piyada; Scholz, Brett; Roper, Cath; Happell, Brenda
Abstract: Goals of the mental health consumer movement include redressing inequality and increasing consumer leadership across the mental health sector. A means of achieving these goals is empowerment of consumers at systemic levels of the mental health sector. There have been calls for research to focus on allies – those who use their power to support and advocate for the goals of the consumer movement. This study aimed to examine the role of allies in consumer empowerment. Semi‐structured interviews were conducted with 15 individuals (including three consumers, nine allies, and three participants each identifying as both consumer and ally). Findings suggest that allies cannot directly empower consumers but should support opportunities for consumer leadership within the sector. We discuss how allies might do this and avoid paternalism in their allyship.